1970
DOI: 10.1163/187631270x00357
|View full text |Cite
|
Sign up to set email alerts
|

An Aphid Sex Attractant

Abstract: The experiments described have given the following conclusions: (I) A chemical signal (pheromone) emitted by the oviparous female has an attractive effect upon the males. This signal is not emitted by the virginogeniae. (2) The signal is emitted by organs situated on the hind tibiae of the oviparous female and perceived by organs on the male antennae. (3) The substance is only emitted by the females during a certain period in their lifetime. Apparently, this is principally the condition which has been called a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
116
0
3

Year Published

1973
1973
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(119 citation statements)
references
References 0 publications
0
116
0
3
Order By: Relevance
“…A 4-way olfactometer (Pettersson, 1970;Vet et al, 1983) was used to test the behavioural response of adult D. tetensi to hostplant odours. The olfactometer comprised of two glass sections measuring 115 mm × 115 mm × 18 mm (width × length × height).…”
Section: Methodsmentioning
confidence: 99%
“…A 4-way olfactometer (Pettersson, 1970;Vet et al, 1983) was used to test the behavioural response of adult D. tetensi to hostplant odours. The olfactometer comprised of two glass sections measuring 115 mm × 115 mm × 18 mm (width × length × height).…”
Section: Methodsmentioning
confidence: 99%
“…First Gold). The traps operated during July [8][9][10][11][12][13][14][15][16][17][18][19][20]1996 and were emptied and the treatments were rerandomized daily. Numbers of spring migrants of the damson-hop aphid, Phorodon humuli, in the daily trap catches were counted and the data were subjected to ANOVA.…”
Section: Gc-mass Spectrometry (Ms)mentioning
confidence: 99%
“…conspecific mating, attraction, sex pheromone, olfactometer, nepetalactol, nepetalactone, Homoptera, Aphidae, Acyrthosiphon pisurn, Aphis fabae, Megoura viciae lntroduction Pettersson (1970aPettersson ( , 1971 and Marsh (1972) first observed that sexual female aphids (oviparae) released a sex pheromone which attracted males. The pheromone was released from scent plaques on the hind tibiae and detected by olfactory sensilla on male antennae.…”
Section: Introductionmentioning
confidence: 99%